2023
DOI: 10.1186/s40634-023-00613-z
|View full text |Cite
|
Sign up to set email alerts
|

Slight pelvic obliquity is normal in a healthy population: a cross‐sectional study

Abstract: Purpose Pelvic obliquity (PO) has not been extensively investigated, and there is no gold standard for measurement. The PO is essential for surgeons in planning hip arthroplasty, which includes the restoration of leg length discrepancy (LLD). We aimed to establish a normative range of PO angles by measuring healthy individuals without musculoskeletal disorders. Methods Our study included 134 consecutive cases (70 females) referred to our institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The size of the study sample was considered adequate to achieve statistical significance with a = 0.05, with an 80% power and effect size (f) = 0.25 (calculated based on a partial η 2 = 0.06), based on an a priori power analysis using an online power analysis application (G*Power v. 3.1.9.2; Universität Düsseldorf: Psychologie – HHU, Düsseldorf, Germany). Individuals with musculoskeletal soft tissue or joint injuries of the lower limb, pathological conditions that could prevent normal walking and running, or a leg length discrepancy of >5 mm, as well as excessive skeletal deviations in the trunk (e.g., >5.0° of rotation of the thoracic or lumbar spine when performing the Adam’s test indicative of ≥20° scoliosis), pelvis (e.g., >2° obliquity [ 41 ]), and feet (e.g., overpronation or supination as defined by the Foot Posture Index-6, (FPI-6 [ 42 ])), were excluded from the study. All inclusion/exclusion criteria that were related to prior lower extremity injuries and frontal plane body deviations were selected based on the clinical applicability and the potential impact that they could have on the study variables.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the study sample was considered adequate to achieve statistical significance with a = 0.05, with an 80% power and effect size (f) = 0.25 (calculated based on a partial η 2 = 0.06), based on an a priori power analysis using an online power analysis application (G*Power v. 3.1.9.2; Universität Düsseldorf: Psychologie – HHU, Düsseldorf, Germany). Individuals with musculoskeletal soft tissue or joint injuries of the lower limb, pathological conditions that could prevent normal walking and running, or a leg length discrepancy of >5 mm, as well as excessive skeletal deviations in the trunk (e.g., >5.0° of rotation of the thoracic or lumbar spine when performing the Adam’s test indicative of ≥20° scoliosis), pelvis (e.g., >2° obliquity [ 41 ]), and feet (e.g., overpronation or supination as defined by the Foot Posture Index-6, (FPI-6 [ 42 ])), were excluded from the study. All inclusion/exclusion criteria that were related to prior lower extremity injuries and frontal plane body deviations were selected based on the clinical applicability and the potential impact that they could have on the study variables.…”
Section: Methodsmentioning
confidence: 99%
“…Herrington showed that the pelvis was tilted anteriorly by no more than 7° in most of the asymptomatic population studied [ 9 ]. In a recent study, Moharrami et al identified pelvic obliquity ranging from 0° to 5.6° in male and female individuals considered part of the normal population [ 10 ]. In essence, the outcomes of these studies suggest that the pelvis in the general population undergoes positional shifts influenced by both internal forces from capsuloligamentous structures and muscles, as well as external impacts arising from daily activities such as interactions with the ground.…”
Section: Introductionmentioning
confidence: 99%